Feminist Perspective of Community Development Practices in Nepal - Pokharel, Bandana; Timsina, Tirtha Raj; Khatri, Bishnu Bahadur (Far Western Review, 2024)
Feminist perspective of community development encompasses the gender sensitive development practices to ensure the equitable share of benefits and progress to all community members regardless of gender disparity. This research paper aims to examine the current status of gender inequality and the application of feminist principles into community development initiatives in Nepal as a pathway for achieving gender equality. This paper has prepared in a descriptive research design which is based on the secondary information collected from different scholarly published sources such as journal article, edited books, publication of government and other organization along with online database through official websites of respective organizations, Google scholar, NepJOL and so on. The findings reveal that incorporating feminist principles in community development practices can result in positive outcomes such as increased participation of women and leadership in decision-making processes and improved access to resources and services. It concludes that incorporating feminist principles into community development initiatives can play pivotal role in achieving gender equality, reduced gender-based violence and promoting inclusive and sustainable development in Nepal. Therefore, the study suggests that it is essential to implement targeted capacity-building programs to empower women with essential skills and knowledge, ensuring their active participation and leadership in community development initiatives to promote gender equality and inclusive progress in Nepal.